Skin Diseases and their Treatment Strategies in Sub-Saharan African Regions - Anwar, Esra T.; Gupta, Nandan; Porwal, Omji; Sharma, Akanksha; Malviya, Rishabha; Singh, Amit; Fuloria, Neeraj Kumar (Infectious Disorders - Drug Targets, 2022)
Background: In the rural areas of sub-Saharan African regions, skin diseases are so common. Due to which the population of the sub-Saharan region suffers from different types of skin disorders. In these regions, many treatment options are not available for the treatment of skin disease. Aim: The current study aims to discuss various skin diseases and their treatment strategies, specifically in sub-Saharan African regions. Methods: Extensive literature survey was carried out by using Scopus, Science Direct, Elsevier, Google scholar and Bentham science databases. Results and Discussion: It was demonstrated from the literature surveys that different effective techniques are used in the management of skin disease. In the result, it was shown that the condition of the disease is at a dangerous level which must be controlled. Conclusion: It is concluded from the manuscript that the skin disorder in the sub-Saharan region is at a very dangerous level. The research must be done to develop a better understanding of the disease and its treatment.
Keywords: Sub-Saharan Africa